2015
DOI: 10.15244/pjoes/26383
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Anti-Cyanobacterial Activity of Essential Oils from Six Different Submerged Macrophytes

Abstract: Allelochemicals from macrophytes or other organisms that inhibit microalgal growth have gained great interest due to their environmental potential as algaecides in controlling water blooms or red tide [1]. In aquatic ecosystems, varieties of submerged macrophytes were found to effectively inhibit the growth of blue-green algae [2]. For example, Myriophyllum spicatum [3][4][5], Vallisneria spiralis [2], Potamogeton crispus [6], Ceratophyllum demersum, and Najas marina [7] showed allelopathic effects on nuisance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Recently, algicidal polyphenolic p-hydroxybenzoic acid, coumarin, and fatty acids have been isolated from different plants [50][51][52]. Wang et al [53] reported the algicidal activities of essential oils from six plant species, namely, Potamogeton cristatus, Potamogeton maackianus, Potamogeton lucens, Vallisneria spinulosa, Ceratophyllum demersum, and Hydrilla verticillata. The inhibition rates of essential oils on M. aeruginosa were 30.2-41.7% at a concentration of 50.0 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, algicidal polyphenolic p-hydroxybenzoic acid, coumarin, and fatty acids have been isolated from different plants [50][51][52]. Wang et al [53] reported the algicidal activities of essential oils from six plant species, namely, Potamogeton cristatus, Potamogeton maackianus, Potamogeton lucens, Vallisneria spinulosa, Ceratophyllum demersum, and Hydrilla verticillata. The inhibition rates of essential oils on M. aeruginosa were 30.2-41.7% at a concentration of 50.0 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [14] were investigated the antibacterial activity of rosemary essential oil on K. Pneumoniae in aiding of MIC technique, the results exhibited a remarkable impact on the biofilm of this bacteria by inhibition the initial cell attachment. Essential oil of rosemary showed antagonistic activity against 60 strains of multidrug resistant E.coli isolated from many specimens: the respiratory tract, abdominal cavity, urinary tract, skin and from hospital equipment.…”
Section: Figure (1) Antagonistic Activity Of Rosemary Essential Oil Amentioning
confidence: 99%
“…Therefore, concentrations of chl a, usually representative of phytoplankton biomass, remain high in HERB-EXCR. In contrast, the low concentrations of chl a in EXCR may be a result of submerged macrophytes inhibiting the growth of phytoplankton through competition for light, nutrients, and/or allelopathic effects [34][35][36].…”
Section: Effects On Water Qualitymentioning
confidence: 99%